Potret Diskriminasi Terhadap Kelompok Minoritas Ahmadiyah di Media Online - Siti Khodijah Nurul Aula (UIN Sunan Kalijaga Yogyakarta, 2021)
This study analyzes a collection of news from online mass media related to the violence experienced by Ahmadiyah in the last 10 years in the mass media. Stigma about Ahmadiyya which is subject to persecution and discrimination from irresponsible elements. Reporting in the mass media in addition to providing updated information, on the other hand also provides a social deterrent effect that prevents such incidents from happening again. There are two problems that will be raised in this research, (1) How does the media portray the persecution-discrimination experienced by Ahmadiyah in Indonesia? (2) To what extent has the news coverage in the media influenced the reduction of persecution and discrimination against Ahmadiyah? The collected data is then analyzed with one of the theories about the five functions of the media including surveillance, interpretation, linkage, transmission of values, and entertainment in order to see the extent of the conflict. that occurred and efforts to break the chain of violence in the Ahmadiyah case. This study concludes that the news in the mass media that is transmitted on social media does not have a significant impact in reducing cases of violence against the Ahmadiyya group. The mass media provide benefits in terms of publication and dissemination of information, but do not have a direct effect on conflict resolution. Conflict resolution in the Ahmadiyah case still requires encouragement from legal regulations and awareness of religious community members.